Model Inovatif Pendidikan Agama Islam untuk Era Society 5.0: Sintesis Konstruktivisme, Heutagogi, dan TPACK: Tinjauan Pustaka Sistematis dan Analisis Isi - Muhammad Hanan Putra Ardani; Muhammad Arifin; Eko Ngabdul Shodikin (Program Studi Pendidikan Agama Islam, 2025)
The Society 5.0 requires education that is human-centered while meaningfully utilizing digital technology. Islamic Religious Education (IRE) in many institutions still faces challenges such as one-way instruction, varying levels of teachers’ digital literacy, and curricula not yet integrated with contemporary needs. This study aims to formulate an innovative IRE model relevant to Society 5.0 through a systematic literature review and content analysis to map key themes, gaps, and implications for reform. The synthesis produces an integrated design based on three theoretical foundations: social constructivism, heutagogy, and technological pedagogical content knowledge (TPACK). The model is embodied in three pillars: digital transformation of learning, value- and digital-manners-based learning, and project-based learning that links scriptural principles with real-world issues. Evaluation is conducted authentically through layered assessments, including cognitive tests, collaboration records, platform analytics, and learners’ reflective journals. The integration of theory, technology, and character enhances the relevance and effectiveness of learning, provided that teacher capacity, ethical data governance, and minimum infrastructure are strengthened. This model offers a measurable roadmap for reorienting Islamic Religious Education toward contextual, humanistic, and transformative learning